Sepedi oral poetry with reference to kiba traditional dance of South Africa - Maahlamela, Tebogo David (Rhodes University, Faculty of Humanities, School of Languages, 2018)
Previous studies show that contrary to other African languages of fewer speakers, written poetry in Sepedi/Sesotho sa Leboa's transition from oral to written did not only lag behind, its development was also slow, with less intense treatment. However, this scarcity is not of the actual oral material, but rather its documented version. Vast untreated material at various repositories such as the South African Broadcasting Corporation (SABC) library and the International Library of African Music (ILAM) are facing a risk of being lost due to limited resources and resourcefulness to digitalise them. Investigation of written poetry from 1906 to 2006 attests to the fact that in its written form, Sepedi/Sesotho sa Leboa poetry is still underdeveloped, dominated by "microwaved" collections aiming at nothing beyond meeting school prescription criteria. Calls have been made from the dominant South African poetry narrative that there are no innovative studies in the field of African languages, especially Sepedi/Sesotho sa Leboa. Musicological studies show that contemporary jazz artists have adopted and adapted kiba poetry into jazz music, which resulted into classics of all times. Intensive studies were conducted on such poetic kiba-influenced jazz, but the primary source remains a grey area. The analysis of selected kiba poems shows that kiba poetry is the richest poetic form in the Sepedi/Sesotho sa Leboa with its creative and artistic merit exceeds all other genres. The study further reveals that kiba poetry is the heart of Bapedi/Basotho ba Leboa spirituality, a heart without which some faith institutions will remain incomplete. Furthermore, kiba poetry embodies, among others, poetic genres rarely explored in the South African poetry milieu such as "sound poetry" and poetry of special metrical schemes, of dramatic and devotional essence. Scholarly attention is, therefore, recommended on this repertoire to explore the field beyond this preliminary study, so as to save as many kiba poems as possible, which will enrich the dwindling written poetry milieu. Literary excellence of the treated poems attests to the fact that the artistic wealth of kiba poetry is worthy of attention, and it has potential to transform not only the face of poetry in Sepedi/Sesotho sa Leboa, but of the entire South African poetry landscape.
Keywords: Northern Sotho poetry; Northern Sotho poetry -- History and criticism; Folk songs, Northern Sotho; Sound poetry -- South Africa; Archival materials -- Conservation and restoration; Spiritualism in literature; Cultural appropriation; Folk poetry, Northern Sotho; Kiba traditional dance; Kiba poetry